DAYA SAING USAHA TERNAK SAPI PERAH RAKYAT DI KECAMATAN PUJON KABUPATEN MALANG JAWA TIMUR - Harmini adibowo; Feryanto willcharo (Media Ekonomi, 2014)
Up to present, the dairy farmers only able to meet 25-30 percent of all milk demand in Indonesia, although milk and its derivatives continues to increase steadily. This condition occurs due to low milk productivity, small-scale dairy farm unit, inadequate government policies as well as economic globalization. The objectives of this study are, first, to measure the competitiveness of the small-scale dairy farm. Second, to evaluate the impact of government policies. Third, lastly, to analyse the implication of price changes on input-output. A Policy Analysis Matrix (PAM) for data is applied. The results show that, first, the small-scale dairy farms operate in competitiveness. Second, so far government policies did not provide adequate incentives and directly promote the dairy farms’ competitiveness. Third, high import tariff (15 percent) could significantly protect the competitiveness of the small-scale dairy farms.